2014
DOI: 10.1038/onc.2013.577
|View full text |Cite
|
Sign up to set email alerts
|

ASC deficiency suppresses proliferation and prevents medulloblastoma incidence

Abstract: Apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) is silenced by promoter methylation in many types of tumors, yet ASC’s role in most cancers remains unknown. Here, we show that ASC is highly expressed in a model of medulloblastoma, the most common malignant pediatric brain cancer; ASC is also expressed in human medulloblastomas. Importantly, while ASC deficiency did not affect normal cerebellar development, ASC knock-out mice on the Smoothened (ND2:SmoA1) transgenic model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
6
1
Order By: Relevance
“…We also found that overexpression of PYCARD significantly promoted cell proliferation and migration ability after TMZ treatment; conversely, the loss of PYCARD decreased cell proliferation and migration ability. However, no noticeable apoptotic and half-maximal inhibitory concentration (IC 50 ) changes were observed in our research (30)(31)(32)(33). This is inconsistent with the previous results (32), and this discrepancy is due to cancer heterogeneity and the complex network regulating mRNA.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We also found that overexpression of PYCARD significantly promoted cell proliferation and migration ability after TMZ treatment; conversely, the loss of PYCARD decreased cell proliferation and migration ability. However, no noticeable apoptotic and half-maximal inhibitory concentration (IC 50 ) changes were observed in our research (30)(31)(32)(33). This is inconsistent with the previous results (32), and this discrepancy is due to cancer heterogeneity and the complex network regulating mRNA.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies have found PYCARD deficiency suppresses proliferation and prevents medulloblastoma incidence (30). We also found that overexpression of PYCARD significantly promoted cell proliferation and migration ability after TMZ treatment; conversely, the loss of PYCARD decreased cell proliferation and migration ability.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In agreement with a tumor suppressor function, ASC methylation correlated with poor prognosis in non-small-cell lung cancer [39], oral squamous cell carcinoma [40] and gastric cancer [41]. On the other hand, in another study [42], high expression of ASC in oral cavity squamous cell carcinoma correlated with poor patients’ survival and in a medulloblastoma mouse model ASC genetic deletion markedly reduced proliferation, hyperplasia and mortality [43]. In addition, in myeloid cells ASC, as an inflammasome adaptor molecule, is required for IL-1β processing and activation.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, knockdown of SMAD5 by overexpressing the miR-155 expression enhanced the aggressiveness of diffuse large B cell lymphoma in vivo [ 52 ]. On the other hand , increased expression of SMAD5 was found to reduce proliferation of cerebellar granule neuron progenitors [ 53 ],and induce apoptosis which may have a negative impact on the proliferative activity of the cells [ 54 ]. As far as MSK1 is concerned, inhibition of MSK1 resulted in a marked increase in cell production during mouse pancreatic development [ 55 ].…”
Section: Discussionmentioning
confidence: 99%